Kontribusi Penerapan Bahan Ajar Model Inkuiri Terbimbing Ditinjau Dari Kompetensi Fisika Peserta Didik SMAN 9 Padang - Widya Nofitri; Djusmaini Djamas; Amali Putra (PILLAR OF PHYSICS EDUCATION, 2018)
The physics achievement of student is still low. Observation results in several high schools in the city of Padang, one of the causes learning material used has not been able to provide adequate achievement of competence for students. This study aims to determine the significant effect on the use of learning material oriented guided inquiry methods to the achievement of student competence on learning physics class X SMAN 9 Padang in the academic year 2017/2018. This type of research is a quasi experiment with Randomized Control Group Only Design. The study population is all students of class X MIPA SMAN 9 Padang. Sampling is done by Cluster Random Sampling technique. The sample of this research is class X MIPA 2 as control class and class X MIPA 4 as experiment class. The data of this research include attitude, knowledge, and skill competency data. Taking on attitude competence using observation sheet, while for knowledge competence with test and skill of data obtained with obervation sheet with scoring section. Data analysis for attitude competence is processed by percentage technique and presented in graph form. In the competence of knowledge and skill is processed by t test, followed by simple regression analysis after fulfilling the requirements of analysis. The result of data analysis shows for the experiment class attitude competence is higher than the control class. For the knowledge competence after the test, the average of experimental class is 75,52 while the control class average is 69,09. On the achievement of the experimental class skill competence of 82.81 while the control class average of 78,38. The result of correlation analysis on knowledge and skill competence obtained rxy 67% and 23%. The result of this research can be concluded that there is influence which means the use of learning material oriented guided inquiry method to student competence on learning physics class X SMAN 9 Padang.